Electrophysiologic Evaluation of the Facial Nerve and Blink Reflex Pathways in Asymptomatic Cochlear Implant Users. (22nd July 2016) - Edizer, Deniz Tuna; Adatepe, Turgut; Uzun, Nurten; Yigit, Ozgur; Gunduz, Aysegul; Yildiz, Muhammet; Celebi, Ozlem Onerci
Abstract : Objective: To evaluate the functional integrity of the facial nerve and blink reflex (BR) pathways in asymptomatic patients who underwent cochlear implantation (CI). Study Design: Case series with planned data collection. Setting: Tertiary referral center. Subjects and Methods: Twenty‐four deafened patients with unilateral CI who had no complications were enrolled. Bilateral compound muscle action potentials (CMAPs) of the facial nerve were recorded over the nasalis and occipitalis muscles, whereas BR responses were recorded over the orbicularis oculi after supraorbital nerve stimulation. All recordings were performed when the external part of the implant was in place (CIp) and after its removal (CIr), except occipitalis recordings, which were performed only after removal. The amplitude and latency of CMAP were measured to evaluate the axonal integrity of the zygomatic and posterior branches of the facial nerve. Latency, amplitude, and duration of the BR were measured to investigate the integrity of trigeminofacial connections. Results: The amplitude and latency of CMAP over the nasalis muscle were bilaterally normal, and the difference between CIp and CIr was not statistically significant. No CMAP of the occipitalis muscle was recorded in 4 (16.7%) patients, and low‐amplitude responses were recorded on the implant side of 20 (83.3%). Amplitudes of the contralateral R2 response were higher in the CIp condition versus the CIr condition ( P =. 031). There were no differences among other BR components. Conclusion: During functioning of the CI system, excitability of the facial circuit may increase either through the facial motor nucleus or through removal of the inhibitory effect of the descending pathway.